Rectified electroosmotic flow in microchannels using Zeta potential modulation – Characterization and its application in pressure generation and particle transport - Wu, Wen-I (My University, 2012)
Microfluidic devices using electroosmotic flows (EOFs) in microchannels have been developed and widely applied in chemistry, biology and medicine. Advantages of using these devices include the reduction of reagent consumption and duration for analysis. Moreover the velocity profile of EOFs, in contrast to the parabolic profile found in pressure-driven flows, has a plug-like profile which contributes significantly less to solute dispersion. It also requires no valve to control the flow, which is done with the appropriate application of electrical potentials, thus becomes one of the favourite techniques for sample separation. However, high potentials of several hundred volts are usually required to generate sufficient EOF. These high potentials are not practical for general usage and could cause electrical hazard in some applications. One of the possible solutions is the introduction of zeta potential modulation. The EOF in a microchannel can be controlled by the zeta potential at the liquid/solid interface upon the application of external gate potentials across the channel walls. Combined with AC EOF, it can rectify the oscillating flows and generate pressure that can be used for microfluidic pumping applications. Since the flow induced by the alternating electric field is unsteady and periodic, it is critical to visualize the flow with high spatial and temporal resolutions in order to understand fluid dynamics. A novel method to obtain high temporal resolution for high frequency periodic electrokinetic flows using phase sampling technique in micro particle image velocimetry (PIV) measurements are first developed in order to characterize the AC electroosmotic flow. After that, the principle of zeta potential modulation is demonstrated to transport particles, cells, and other micro organisms using rectified AC EOF in open microchannels. The rectified flow is obtained by synchronous zeta-potential modulation with the driving potential in the microchannel. Subsequently, we found that PDMS might not be the best material for some pumping and biomedical applications as its hydrophobic surface property makes the priming process more difficult in small microchannels and also causes significant protein adsorption from biological samples. A more hydrophilic and biocompatible material, polyurethane (PU), was chosen to replace PDMS. A polyurethane-based soft-lithography microfabrication including its bonding, interconnect integration and in-situ surface modification was developed providing better biocompatibility and pumping performance. Finally, an electroosmotic pumping device driven by zeta potential modulation and fabricated by PU soft lithography was presented. The problem of channel priming is solved by the capillary force induced by the hydrophilic surface. Its flow rate and pressure output were found to be controllable through several parameters such as driving potential, gate potential, applied frequency, and phase lag between the driving and gate potentials.
Keywords: microfluidics; zeta potential; electroosmotic flow; polyurethane; particle image velocimetry; Biomechanical Engineering; Biomechanical Engineering